Answer:
3 (5x+2y = 0)
2 (2x – 3y = -19)
Step-by-step explanation:
5x+2y=0 (1)
2x-3y=-19 (2)
To eliminate y from the first two equation when applying the linear combination method
We will multiply y Equation (1) and (2) with 3 and 2 respectively so that the coefficients of y in the two equations +6 and -6 respectively
3(5x+2y=0)
2(2x-3y=-19)
We have,
15x+6y=0 (3)
4x-6y= -38 (4)
Add Equation (3) and (4)
19x=-38
x= -2
Substitute x= -2 into (1)
5x+2y=0
5(-2)+2y=0
-10+2y=0
-10= -2y
y=-10/-2
=5
y=5, x=-2
D. 53, 107
The pattern is multiplying the previous number by two and then adding one to it.
reflection of
over the y axis we get 
Step-by-step explanation:
We need to find the reflection of f(x)=sqrt x over the y axis
So, reflection over y- axis
If the function f(x) is transformed over y-axis then the new function g(x) will be 
So, finding reflection of
over the y axis we get:

So, reflection of
over the y axis we get 
Keywords: Transformations
Learn more about Transformations at:
#learnwithBrainly